Kesejahteraan psikologis dalam hubungannya dengan kecemasan dan dukungan sosial - Indriyati Eko Purwaningsih; Ryan Sugiarto; Sulistyo Budiarto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
This research was backgrounded by indications of a lack of psychological well-being in society. The purpose of this study was to empirically test the relationship between anxiety as well as social support and psychological well-being of people in Karang Rejek Village, Wonosari District, Gunungkidul, Yogyakarta. Sampling was carried out by accidental sampling method. There are 98 samples in total. Data was collected using the scale: psychological well-being, anxiety, and social support. The content validity test shows that the three scales used are valid, and measure all of its dimensions. The reliability coefficient of the psychological well-being scale is rxx1: 0.821, the anxiety scale is rxx1: 0,894, and the social support scale is rxx1: 0.879. The result of hypothesis testing which was carried out using multiple regression technique yielded a value of F: 25.813 and p: 0.000 (p<0.05). This research concludes that: The first hypothesis is accepted, there is a significant relationship between anxiety and social support variables and psychological well-being variable. Both contributed 59.3 % to the criteria variable altogether. The second hypothesis test produced a beta coefficient price b: - 0. 258, t: - 2.255, and p: 0,026 (p<0.05). Thus, the hypothesis is also accepted. Furthermore, the third hypothesis test produced beta coefficient b: 0.702, t: 5.158, p: 0.000 (p<0.05), showing that the hypothesis is likewise accepted. Referring to these results, this study shows the importance of reducing anxiety and increasing social support to maintain and improve psychological well-being in society.